Study on thermal degradation mechanism of heat-resistant epoxy resin modified with carboranes. (June 2020) - Cui, Meili; Zhang, Lili; Lou, Pingping; Zhang, Xuezhong; Han, Xiaojie; Zhang, Zhijie; Zhu, Shuhua
Abstract: To generate a novel heat-resistant phenolic epoxy resin, carborane containing curing agent (1, 7-bis(aminophenylene)meta-carborane) was synthesized and applied to cure the resin. The generated carborane-containing phenolic epoxy resin showed better thermal stability and thermal oxidative stability than carborane free phenolic epoxy resin. And the Lap Shear Strength of bonding samples showed the improved bonding performances. The thermal degradation mechanism of carborane-epoxy resin was investigated and the results showed that the carborane of samples was gradually oxidized to B2 O3 at high temperatures, which covered at the surface of the adhesives to maintain the thermal resistance at high temperature.